The Role of Epstein-Barr Virus in Adults With Bronchiectasis: A Prospective Cohort Study. (19th June 2020) - Chen, Chun-Lan; Huang, Yan; Martinez-Garcia, Miguel Angel; Yuan, Jing-Jing; Li, Hui-Min; de la Rosa-Carrillo, David; Han, Xiao-Rong; Chen, Rong-Chang; Guan, Wei-Jie; Zhong, Nan-Shan
Abstract: Background: Epstein-Barr virus (EBV) is implicated in the progression of chronic obstructive pulmonary disease. We aimed to determine whether EBV correlates with bronchiectasis severity, exacerbations, and progression. Methods: We collected induced sputum in healthy controls and spontaneous sputum at 3–6-month intervals and onset of exacerbations in bronchiectasis patients between March 2017 and October 2018. EBV DNA was detected with quantitative polymerase chain reaction. Results: We collected 442 sputum samples from 108 bronchiectasis patients and 50 induced sputum samples from 50 healthy controls. When stable, bronchiectasis patients yielded higher detection rates of EBV DNA (48.1% vs 20.0%; P = .001), but not viral loads (mean log10 load, 4.45 vs 4.76; P = .266), compared with controls; 64.9% of patients yielded consistent detection status between 2 consecutive stable visits. Neither detection rate (40.8% vs 48.1%; P = .393) nor load (mean log10 load, 4.34 vs 4.45; P = .580) differed between the onset of exacerbations and stable visits, nor between exacerbations and convalescence. Neither detection status nor viral loads correlated with bronchiectasis severity. EBV loads correlated negatively with sputum interleukin-1β ( P = .002), CXC motif chemokine-8 ( P = .008), and tumor necrosis factor–α levels ( P = .005). Patients initially detected with, or repeatedly detected with, EBV DNA had significantly faster lung function decline and shorter time to next exacerbations (both P < .05) than those without. Detection of EBV DNA was unrelated to influenza virus and opportunistic bacteria (all P > .05). The EBV strains detected in bronchiectasis patients were phylogenetically homologous. Conclusions: Patients with detection of EBV DNA have a shorter time to bronchiectasis exacerbations. EBV may contribute to bronchiectasis progression. Abstract : The role of chronic viral infections in bronchiectasis is unclear. In this prospective study, we summarize the association between viral loads or detection rate and the clinical status as well as inflammatory response of bronchiectasis.